STUDIES ON THE OCCURENCE AND GROWTH RATE OF TWO INTERTIDAL FOULING BRYOZOANS IN THE MATTANCHERRY CANNEL OF COCHIN HARBOUR, SOUTH- WEST COAST OF INDIA - NAIR, N UNNIKRISHNAN (Fishery Technology, 2025)
Occurrence and growth rates of two species of intertidalfouling bryozoans namely Electra bengalensis (Stoliczka) andElectra crustulanta (PaHas) are presented in this paper. The formerwas a typically marine form, settling on panels only during thehigh saline conditions of the premonsoon period and were absentduring the low salinity conditions of the monsoon period, while thelatter appeared to be a typical brackish water form settling onpanels during the Jow saline conditions existing during the monsoonand postmonsoon periods and were totally absent during thepremonsoon months. Regression co-efficient of the former washigher th~m that of the latter suggesting more pronounced growthin Electra bengalensis. Maximum growth for this species wasnoticed during March, April and May (pre-monsoon) while forthe other species growth was more or less similar during monsoonand postmonsoon months (June-January) showing that the specieswas at home in oHgohaHne and mesohaHne waters.